Exploring Medical Cannabis Knowledge and Attitudes among Health Care Providers in Northern Thailand After Legalization - Likhitsanpoo, Paritat; Wang, Bunsita; Sowtivech, Nutcha; Thaisanga, Ponlawat; Nothao, Pornsawat; Lin, Wannasa; Chompoosri, Poom; Tangchitphisut, Paween (Greater Mekong Subregion Medical Journal, 2025)
Background: In June 2022, the Ministry of Public Health of Thailand announced the legalization of cannabis for medical and recreational purposes under controlled conditions. However, despite this regulatory shift, there exists a paucity of evidence-based research regarding the therapeutic efficacy of cannabis. Moreover, within the Thai context, there persists a notable gap in understanding the comprehensive spectrum of health benefits and concerns associated with cannabis usage. Objective: To investigate the knowledge and attitudes of healthcare providers regarding medical cannabis. Materials and Methods: This cross-sectional study was conducted among healthcare providers at Mae Fah Luang University Medical Center Hospital (MFU-MCH) and the Thai-Chinese Medicine Institute (TCMI) in November 2022. The survey instrument comprised two components. Firstly, it evaluated the participants’ foundational knowledge concerning medical cannabis. Secondly, it measured their attitudes toward medical cannabis utilizing a Likert Four-Point scaling system. Data were collected through online surveys administered via Google Form. Results: 74 healthcare providers were recruited. The prevalence of low knowledge scores was found to be 13.51%. Attitudes toward medical cannabis use were evenly split, with 50% expressing agreement and 50% expressing disagreement. Conclusion: Basic knowledge about cannabis appears to be limited among healthcare providers, while attitudes towards its medical use are evenly split. Given that healthcare providers play a crucial role in advising patients and the public on medical cannabis, there is a pressing need to enhance their knowledge in this area.